Challenges of international market selection – the perspective of Mexican and Brazilian multilatinas - Maciel, João; Radomska, Joanna; Costa e Silva, Susana (Contemporary organisation and management. Challenges and trends, 2020)
Multilatinas have become a phenomenon that has caught the attention of many authors and researchers around the world. This paper was developed to understand their international market selection process and the challenges they face. We hypothesized that these companies ground their international expansion on the basis of physical proximity. The CAGE framework developed by Ghemawat measures the distance between two countries according to Cultural, Administrative, Geographic and Economic criteria and was the main indicator for this research. The literature review allowed for the exploration of concepts related to Multilatinas’ expansion, such as emerging market multinational companies management, internationalization process, market selection, and the CAGE framework. The systematic and opportunistic way of selecting markets were also studied in the development of a framework used to understand how managers from Mexican and Brazilian Multilatinas decide on market selection and which factors they take into account in that decision process. It was possible to verify that countries where Mexican and Brazilian Multilatinas expand are the ones with the lowest overall CAGE distance.